Method of flash evaporation and condensation – heat pump for deep cooling of coal-fired power plant flue gas: Latent heat and water recovery. (15th June 2016) - Li, Yuzhong; Yan, Min; Zhang, Liqiang; Chen, Guifang; Cui, Lin; Song, Zhanlong; Chang, Jingcai; Ma, Chunyuan
Graphical abstract: Highlights: A method is developed for deep cooling of flue gas in coal-fired boilers. The method can recover both latent heat and water from flue gas. The method utilizes FGD scrubber as a deep cooling exchanger. The method adopts the direct heat exchange mode to avoid the corrosion problem. Abstract: Flue gas waste heat recovery and utilization is an efficient means to improve the energy efficiency of coal-fired power plants. At present, the surface corrosion and fouling problems of heat exchanger hinder the development of flue gas deep cooling. In this study, a novel flue gas deep cooling method that can reduce flue gas temperature below the dew point of vapor to recover latent heat and obtain clean water simultaneously is proposed to achieve improved energy efficiency. The heat transfer mode of this method is the direct contact mode, which takes the scrubber, e.g. the flue gas desulfurization (FGD) scrubber, as the deep cooling exchanger. The flash evaporation and condensation (FEC) device and heat pump (HP) are utilized to provide low-temperature medium, such as FGD slurry or water, for washing and deep cooling flue gas, to collect recovered water, and to absorb recovered waste heat. This method is called as the FEC–HP method. This paper elaborated on two optional models of the proposed method. The mechanism for recovering heat and water was also analyzed using the customized flue gas humidity chart, and the method to quantitate recovered heat and water, as well as the results of the case of a 300 MW coal-fired generator set were provided. Net present value calculations showed that this method is profitable in the scenario of burning high-water-content coals. Several potential advantages of this method and suggestions for practical application were also discussed.